2015
DOI: 10.1155/2015/861874
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Chemoorganotrophic Bioleaching Microorganisms to Heavy Metal and Alkaline Stresses

Abstract: The bioleaching potential of the bacterium Bacillus mucilaginosus and the fungus Aspergillus niger towards industrial residues was investigated by assessing their response towards various heavy metals (including arsenic, cadmium, cobalt, chromium, nickel, lead, and zinc) and elevated pH. The plate diffusion method was performed for each metal to determine the toxicity effect. Liquid batch cultures were set up for more quantitative evaluation as well as for studying the influence of basicity. Growth curves were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
0
4
0
1
Order By: Relevance
“…As primary resources become scarcer enhanced landfill mining will become more feasible. However, strategic policy decisions and tailored support systems for enhanced landfill mining is sustained by standardized life cycle assessment frameworks and will be indispensable to remove the remaining non-technical barriers [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As primary resources become scarcer enhanced landfill mining will become more feasible. However, strategic policy decisions and tailored support systems for enhanced landfill mining is sustained by standardized life cycle assessment frameworks and will be indispensable to remove the remaining non-technical barriers [37].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal growth conditions for microorganisms must be maintained in order to assure the resistance of microbes to the metals and get a good efficiency of bioprocesses. [37].…”
Section: Bio-metallurgy: a Way For Futurementioning
confidence: 99%
“…In the study conducted by Yiğit et al (2013) it was reported that the growth rate of Lactobacillus brevis started to decrease more than 35 ppm cadmium. It has been demonstrated that 100 ppm cadmium concentration has a negative effect on the growth of B. mucilaginosus and A. niger microorganisms (Monballiu et al 2015). The decrease in microorganism concentration may be due to the toxic effect of cadmium in the cell, which effects many metabolic activities including protein synthesis (Çınar, 2003).…”
Section: Figure 1 C Freundii Concentrations At Varying Cadmium Concentrationmentioning
confidence: 99%
“…Farklı derişimlerdeki kadmiyum ve selenyum içeren besi yerinde üretilen C. freundii konsantrasyonu Yiğit ve arkadaşları [15] tarafından yapılan çalışmada 35 ppm'den yüksek kadmiyum konsantrasyonlarında Lactobacillus Brevis'in büyüme hızının azaldığını rapor edilmiştir. 100 ppm kadmiyum konsantrasyonunun B. mucilaginosus ve A. niger mikroorganizmalarının büyümesini olumsuz etkilediği gösterilmiştir [16]. Mikroorganizma konsantrasyonundaki azalma, protein sentezi dâhil birçok metabolik aktiviteyi etkileyen hücredeki kadmiyumun toksik etkisinden kaynaklanıyor olabilir [17].…”
Section: Sonuç Ve Tartışmaunclassified